The safety evaluation of phycocyanin-enriched Galdieria sulphuraria extract using 90-day toxicity study in rats and in vitro genotoxicity studies. (5th June 2020) - Athané, Axel; Demol, Julien; Brosset-Vincent, Sandra; Aguenou, Corinne; Krisa, Stéphanie; Courtois, Arnaud; Griffiths, Hywel; Cagnac, Olivier
The microalgae Galdieria sulphuraria, which belong to the class of cyanidiophyceae, are thermostable at temperatures up to 55°C and have successfully been cultivated under controlled fermentation conditions to produce a protein-rich biomass from which a natural blue proteinaceous pigment, C-phycocyanin can be isolated. The C-phycocyanin has potential use as a colour additive and as a dietary supplement. This C-phycocyanin is resistant to acidic pH down to 2.75, in contrast to the one from Spirulina, which is already used as a colouring agent in agri-food applications. To further promote its use for industrial applications, we report, here, the results of a safety evaluation on a G. sulphuraria extract enriched to 33% C-phycocyanin. This was conducted in a 90-day repeated dose toxicity study in rats at doses from 250 to 4000 mg/kg body weight/day, in bacterial reversal mutation test at doses from 312.5 to 5000 µg/plate and in micronucleus assay at doses from 500 to 2000 µg/mL. Overall, our results indicated that the C-phycocyanin extract from G. sulphuraria did not exert any noteworthy adverse effect of toxicological significance in any of the system used for its safety evaluation, even if some minor changes were observed. According to the 90-day repeated dose toxicity study, no observed adverse effect level of 4000 mg/kg/day could be estimated. In conclusion, this study supports the safety of soluble fraction enriched with C-phycocyanin from G. sulphuraria for its use as food ingredient or supplement.